Pengembangan Aplikasi Penjualan Tiket Acara Ghealways Berbasis Website - Stefan Ariady (UNIVERSITAS KALBIS, 2022)
Ghealways organization is a loyal audience organization for Ghea Indrawari which makes regular events. The research aims to develope a website-based ticket sales application for Ghealways. The website was developed using PHP. The research used the Rational Unified Process (RUP) method as a software development method. The application produced by the researcher is a website-based online ticket sales. The features contained on the website are viewing a list of events, buying event tickets, viewing news about organizations and events that have been held.